Student Expectations of an RN-to-BSN Program: A Qualitative Analysis of Student and Faculty Perspectives - Mary Linton DNP, RN, NNP-E, CNE; Beverly W. Dabney PhD, RN; Linda Knecht MSN, RN; Jamie Koonmen MSN, RN (SAGE Publishing, 2019)
The expansion of RN-to-BSN (registered nurse to Bachelor of Science in Nursing) education is addressing the need for nursing workforce development. However, little is known about what RNs expect from their RN-to-BSN education experience. Lack of understanding of student expectations could lead to student-perceived gaps in service quality. The aim of this study was to explore students' expectations of the RN-to-BSN program compared with the faculty's perceptions of what students expect. A descriptive qualitative research study using structured interviews was conducted at a school of nursing in the Midwest region of the United States. Student and faculty reports revealed the common themes of workload, flexibility, coursework, and support. Congruencies were noted in the areas of workload and coursework, and differences were identified in the areas of flexibility and support. Conducting a gap analysis can be a worthwhile endeavor for educators seeking to understand the needs of their student population. Acknowledging RN-to-BSN student expectations and addressing gaps between their expectations and reality early in the program could improve student perceptions of program quality.